Community Political Participation in Village Head Elections: Community Political Participation in Village Head Elections - Laksito, Grida Saktian; Saputra, Jumadil (International Journal of Humanities, Law, and Politics, 2023)
If there is political behavior on the part of the village community, political socialization, and effective political communication from the candidates to the village head regarding the vision and mission or work program to be implemented, village community political engagement will move smoothly. Application the day before the village head election, political outreach by candidates was typically conducted at a distance and frequently ignored political ethics, such as money politics and terror plots. The majority of candidates for village, heads have a good chance of winning the election since they generally have compact, powerful, and familial networks. Politically powerful individuals typically run for village head positions. Villagers can participate in Pilkades in addition to carrying out activities by becoming campaigners (Jurkam) for one of the village head candidates and disseminating programs that will be achieved, joining active interest groups and supporting one of the village head candidates, getting involved in social programs or village social projects, such as promoting programs that will be achieved and carrying out activities in Pilkades. The findings of study conducted through interviews show how crucial it is to educate and socialise citizens about politics, especially those who must vote. Political activities such as political socialisation and political education can be used in efforts to preserve the political system. The two political communication activities serve as a method for influencing the attitudes and actions of future system recipients and successors. Political socialisation, which aims to influence, alter, and mould attitudes and behaviour based on ideals that are deemed right and beneficial to human life, is frequently linked with political education.